Dragonfly and Damselflies at Gajahwong River in D.I. Yogyakarta Urban District - Zaman, Mokhamad Nur; Purwanto, Pratama Bimo; Iman, Dharfan Ihlasul; Farida; Sari, Astri Martha; Maulany, Siti Lathifah; Luthfika, Muhamad; Rofiah, Ngalimatur; Halimah, Giat Siti; Cahya (Proceeding International Conference on Science and Engineering, 2020)
Dragonflies play an important role as a bio-indicator of environmental cleanliness and controller of other insect populations in nature. This study aims to reveal the population of dragonflies in the Gajah Wong river in urban areas in Yogyakarta. The method used is an exploratory method that is by exploring the Gajahwong river which is located between the southern ring road at Giwangan to the northern ring at Catur Tunggal. The results showed that 16 types of dragonflies and 9 types of damselflies were found there. The species which has the most number is Orthetrum Sabina with 253 individuals, and the less type is Gynacantha Subinterrupta, and Zyxomma Obtusum which only found one individual for each. Whereas for Damselflies most species is Pseudagrion Rubriceps with 255 and Ischnura senegalensis is the less which only has one individual.